Periodic solutions of differential inclusions with retards - Gabor, Grzegorz; Pietkun, Radosław (Topological Methods in Nonlinear Analysis, 2000)
The paper is devoted to study the existence ofperiodic solutions for retarded differential inclusions. The nonsmoothguiding potential method is used and topological degree theory formultivalued maps is applied.